2022
DOI: 10.1088/1748-9326/ac7d63
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms driving ESM-based marine ecosystem predictive skill on the east African coast

Abstract: The extension of seasonal to interannual prediction of the physical climate system to include the marine ecosystem has a great potential to inform marine resource management strategies. Along the east coast of Africa, recent findings suggest that skillful Earth system model (ESM)-based chlorophyll predictions may enable anticipation of fisheries fluctuations. The mechanisms underlying skillful chlorophyll predictions, however, were not identified, eroding confidence in potential adaptive management steps. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In addition, rCHLa skill in the Southern Indian Ocean is also related to ENSO evolution (Figures 4a and 4b). Jeon et al (2022) demonstrated that wind stress forcing caused by ENSO to Indian Ocean teleconnections generates skillful chlorophyll prediction up to 2 years arise from off-equatorial Rossby waves and supplies nutrients in the Indian Ocean.…”
Section: Delayed Effects Of Climate-driven Variability On the Anomalo...mentioning
confidence: 99%
“…In addition, rCHLa skill in the Southern Indian Ocean is also related to ENSO evolution (Figures 4a and 4b). Jeon et al (2022) demonstrated that wind stress forcing caused by ENSO to Indian Ocean teleconnections generates skillful chlorophyll prediction up to 2 years arise from off-equatorial Rossby waves and supplies nutrients in the Indian Ocean.…”
Section: Delayed Effects Of Climate-driven Variability On the Anomalo...mentioning
confidence: 99%